2016
DOI: 10.1128/mbio.00990-16
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Dependent C–F Bond Cleavage Allows the Complete Degradation of 4-Fluoroaromatics without Oxygen

Abstract: Complete biodegradation of the abundant and persistent fluoroaromatics requires enzymatic cleavage of an arylic C–F bond, probably the most stable single bond of a biodegradable organic molecule. While in aerobic microorganisms defluorination of fluoroaromatics is initiated by oxygenases, arylic C–F bond cleavage has never been observed in the absence of oxygen. Here, an oxygen-independent enzymatic aryl fluoride bond cleavage is described during the complete degradation of 4-fluorobenzoate or 4-fluorotoluene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 44 publications
2
48
0
Order By: Relevance
“…It was shown that 3‐F‐benzoyl‐CoA is protonated yielding 3‐fluoro‐dienoyl‐CoA, which is not further converted, whereas 4‐F‐benzoyl‐CoA can be slowly dehalogenated. This results from the strength of the C–F bond . In contrast, as C–Cl and C–Br bonds are weaker, the reaction is more feasible but we also find differences in reaction rates according to the position of the substituent.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…It was shown that 3‐F‐benzoyl‐CoA is protonated yielding 3‐fluoro‐dienoyl‐CoA, which is not further converted, whereas 4‐F‐benzoyl‐CoA can be slowly dehalogenated. This results from the strength of the C–F bond . In contrast, as C–Cl and C–Br bonds are weaker, the reaction is more feasible but we also find differences in reaction rates according to the position of the substituent.…”
Section: Resultssupporting
confidence: 89%
“…When considering the benzoyl‐CoA‐reduction and dehalogenation reaction, Tiedt et al showed differences in elimination reactions between meta ‐ and para ‐substitution of CoA‐halobenzoic acids. Whereas meta ‐substitution leads to spontaneous halogen abstraction by an E2‐elimination reaction, protonation of the anionic intermediate after hydride addition would lead to an unfavorable halo‐dienoyl‐CoA following an E1cB elimination of the para ‐substituent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations